The emergence of a national community health worker programme in South Africa: dimensions of governance & leadership - Schneider, Helene (Department of Public Health and Family Medicine, 2017)
National community health worker programmes are returning to favour across the globe. While such programmes expand access and deepen community engagement in health, they require considerable resources and support to sustain. This thesis seeks to enhance understanding of the system-wide changes and governance and leadership required to implement community health worker programmes at scale. Empirically, it examines the implementation of a community based delivery strategy, referred to as Primary Health Care Ward Based Outreach Teams (hereafter referred to as outreach teams), adopted in South Africa since 2011. These outreach teams are reconfiguring a community based care and support sector that evolved organically in response to HIV, towards a comprehensive approach, integrated into the primary health care system. Located within the field of health policy and systems research and using multi-method (document reviews, interviews, observations) case study research, the thesis describes the evolution of community-based services in South Africa and analyses the adoption and early implementation of the outreach team strategy in two provinces (Western Cape, North West). These case studies highlight the diverse and context specific ways in which the strategy emerged at sub-national level, as a negotiated product of local histories of community based services and new mandates from the top. Drawing on an additional case study in a third province (Gauteng), a cross case analysis inductively identified the challenges facing, and the strategies adopted, by provincial and district managers in implementing the new strategy. It shows how implementation of community health worker programmes is far from linear, and the complex and distributed nature of governance and leadership required, spanning analytic, managerial, technical and political roles. The thesis concludes by proposing a multi-level governance and leadership framework for community health worker programmes at scale. Through this lens it adds a more general understanding on health system governance and leadership. The thesis is presented as four published papers embedded in a narrative, that includes a literature review and cross-cutting discussion.